Effect of Dexmedetomidine as an Adjuvant to Ropivacaine in Brachial Plexus Block - Yadav, Rajiv; Yadav, Ila; Bhandari, Sabin; Poudel, Anju (Birat Journal of Health Sciences, 2025)
Introduction: The purpose of this study was to determine whether dexmedetomidine as an adjuvant to ropivacaine in brachial plexus improves the quality of block in terms of onset, duration of analgesia and assess complications of dexmedetomidine. Objectives: To evaluate the effect of dexmedetomidine as an adjuvant to ropivacaine for brachial plexus block in upper limb surgery To assess onset of sensory and motor blockade, duration of sensory and motor blockade, duration of analgesia and any adverse effects of dexmedetomidine. Methodology: 80 patients of American Society of Anesthesiologists (ASA) physical status I and II undergoing upper limb surgery under brachial plexus block were randomly divided into two groups. Group R received 0.35% ropivacaine, 1.5% xylocaine with adrenaline (30ml) and Group RD received 0.35% ropivacaine, 1.5% xylocaine with adrenaline and dexmedetomidine (30ml). Results: The onset of both sensory and motor block was earlier in Group RD than Group R. They were clinically significant (p value 0.000 for sensory, p value 0.005 for motor). The duration of both sensory and motor block was longer in Group RD than Group R which was statistically significant (p value 0.000 for duration of sensory block, p value 0.000 for duration of motor block). Duration of analgesia was also longer in dexmeditomidine group (p value 0.000). Conclusions: Dexmedetomidine (1mcg/kg) as adjuvant to ropivacaine in brachial plexus block shortens the onset of (sensory and motor) block, prolongs the duration of (sensory and motor) block and duration of analgesia.